The Effects of Physical and Social Context on Evaluations of Captive, Intensive Service Relationships - Conlon, Donald E.; Dyne, Linn Van; Milner, Morgan; Ng, Kok Yee (Academy of Management Journal, 2004)
Expanding a conceptual framework, we differentiated services on the basis of their levels of captivity (the difficulty of a customer’s leaving) and intensity (the number of services performed), arguing that context is especially critical to service delivery when these levels are high. Data from cruise ships generally supported our hypotheses. We report effects of physical and social context on evaluations made by passengers, industry experts, and government regulators. Implications for managers of other service settings are discussed. Understanding evaluations of service organization performance is important because services comprise a rapidly growing sector of the economy (Gutek, 1995; Rothman, 1998). In this work, we argue it is important to acknowledge that different evaluator audiences have different perspectives and criteria for assessing performance (Cyert & March, 1963; Scott & Lane, 2000). Receiving positive evaluations of service performance from multiple perspectives is critical to service firm reputation, customer satisfaction, and long-term firm success (Bowen, Gilliland, & Folger, 1999; Mitchell, Agle, & Wood, 1997; Seiders & Berry, 1998). In the major conceptualization of services to date, Gutek (1995) differentiated service encounters from service relationships. In this research, we build on Gutek’s work and further develop the conceptualization of services by considering two additonal facets: the intensity of service (whether service delivery involves one primary service or multiple services) and the captivity of service (whether it is difficult for the party being served to leave the service setting once service delivery has started). We argue that service setting is especially salient in service relationships characterized by high captivity and high intensity (relationships that